1990
DOI: 10.1139/g90-078
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of the blue aleurone trait in diverse wheat crosses

Abstract: The blue aleurone trait has been suggested as a useful genetic marker in wheat (Triticum aestivum L.). However, little information is available on its transmission in diverse backgrounds and on its use to identify hybrid seed. UC66049, a hexaploid spring wheat with a spontaneous translocation that included the gene for the blue aleurone trait (Ba) from Agropyron elongatum (Host) P.B. (synonymous with Elytrigia pontica (Podp.) Holub), was crossed to seven wheat cultivars to test the transmission of the trait. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 1 publication
1
19
0
Order By: Relevance
“…Both purple-and blue-grain markers could also be used in studies to measure the degree of natural cross pollination, and of gamete transmission, histological observations and pigment characterization (Bolton, 1968;Griffin, 1987;Whelan, 1989;Keppenne & Baenziger, 1990). Knott (1958) and Whelan (1989) stated that it was difficult to establish levels of open pollination because grains with one allele for blue pigment were difficult to separate from those with no blue allele.…”
Section: Use Of the Purple And Blue Grain Charactersmentioning
confidence: 99%
See 2 more Smart Citations
“…Both purple-and blue-grain markers could also be used in studies to measure the degree of natural cross pollination, and of gamete transmission, histological observations and pigment characterization (Bolton, 1968;Griffin, 1987;Whelan, 1989;Keppenne & Baenziger, 1990). Knott (1958) and Whelan (1989) stated that it was difficult to establish levels of open pollination because grains with one allele for blue pigment were difficult to separate from those with no blue allele.…”
Section: Use Of the Purple And Blue Grain Charactersmentioning
confidence: 99%
“…However, the erratic expression of pigmentation in F1 grains and especially the number of years involved to produce the blue-and purple-grained hybrid components would make the use of these characters very conservative. Keppenne & Baenziger (1990) suggested that this character could be used in separating doubled haploids obtained after anther culture. Assuming that the parental plant was heterozygous the doubled haploid plants should have either deep blue aleurone (genotype BaBaBa) or non-blue seeds.…”
Section: Use Of the Purple And Blue Grain Charactersmentioning
confidence: 99%
See 1 more Smart Citation
“…The blue-grained gene of Th. ponticum was designated Ba1 (Jan et al 1981;Keppenne and Baenziger 1990;Dubcovsky et al 1996; http://www. shigen.nig.ac.jp/wheat/komugi/) and was physically mapped to the region of FL0.71-0.80 on the long arm of chromosome 4Ag using a set of translocations that showed different seed colors (Zheng et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…(Keppenne & Baenziger 1990). This gene is present in an important genetic resource UC66049 (Qualset et al 2005).…”
mentioning
confidence: 99%